Pentecostalism and schisms in the Reformed Church in Zambia (1996–2001): Listening to the people - Soko, Lukas (HTS teologiese studies, 2011)
This article is descriptive in nature and a practical theological assessment of the schisms that took place in the Reformed Church in Zambia (RCZ) between 1996 and 2001. It analyses empirical evidence to find an answer to the question why it happened. Pentecostal or charismatic tendencies have challenged the long inherited tradition of mainline churches. Subsequently, Pentecostal or charismatic movements have caused intense conflict in the church between the pro-conservatives and pro-Pentecostals. In the RCZ this led to the formation of the Christian Reformed Church (CRC) in 1999 and the Bible Gospel Church in Africa (BIGOCA) in 2001.